INOVASI GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN SKI DI MTS NEGERI 1 PESAWARAN - Nur Haliza; Imam Syafi’i; Jalaluddin Jalaluddin (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
Teachers are responsible for identifying each student's interests through their abilities. Teachers' skills in determining teaching methods are crucial because they influence the success of the teaching and learning process. By implementing innovation, teachers can increase the attractiveness, engagement, and effectiveness of the learning process. Therefore, it is highly recommended that teachers incorporate innovation into their teaching and learning activities. This study aims to determine teacher innovation in increasing student learning interest in the subject (SKI) at MTs Negeri 1 Pesawaran. This research uses a qualitative approach with a descriptive research type. Data collection techniques were conducted through observation, interviews, and documentation. The informants in this study consisted of Islamic cultural history teachers and class VII students of MTs Negeri 1 Pesawaran. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that SKI teachers implemented learning innovations to increase student learning interest by using the storytelling method as a more engaging and interactive learning approach. The purpose of implementing this method is to foster student learning interest through feelings of enjoyment, interest, attention, and active involvement during the learning process. Through storytelling, the material on Islamic Cultural History is presented in a coherent and easy-to-understand story so that students can better appreciate the historical events being studied. In addition, this method encourages students to actively listen, provide responses, express opinions, and re-present the material according to their understanding. Thus, the application of the storytelling method can create a more lively learning atmosphere and contribute positively to increasing student learning interest.